Guidelines for the diagnosis and treatment of primary aldosteronism -The Japan Endocrine Society 2009 - Nishikawa, Tetsuo; Omura, Masao; Satoh, Fumitoshi; Shibata, Hirotaka; Takahashi, Katsutoshi; Tamura, Naohisa; Tanabe, Akiyo (ENDOCRINE JOURNAL, 2011)
The Japan Endocrine Society (JES) attempted to develop guidelines for the diagnosis and treatment of primary aldosteronism (PA). The Task Force Committee (TFC) was composed of a chair, selected by the JES, and additional experts. Systematic reviews of available evidence for Japanese patients were used to recommend the key treatment and prevention. We have evaluated the methods of screening, confirmatory tests and imaging, plus adrenal vein sampling (AVS). Consensus was guided by systematic review of evidence and discussion during each annual meeting of the JES, plus its related meetings, and by e-mail communication. The drafts prepared by TFC were reviewed successively by the members of Research on Intractable Diseases provided by the Japanese Ministry of Health, Labour and Welfare, and in comments from the JES’s councilors. At each stage of review, TFC received written comments and incorporated suggested changes. In conclusion, all patients with hypertension should be screened for PA, because of the high prevalence of cardiovascular disease and the current low case-detection rate in Japan. Case detection can be performed in hypertensive patients and those with hypokalemia by determining the aldosterone/renin ratio, and the diagnosis of PA can be confirmed by two of three confirmatory tests. The presence of a unilateral aldosterone-producing adenoma should be established/excluded by AVS by an experienced radiologist, optimally followed by laparoscopic adrenalectomy. In contrast, patients with bilateral adrenal hyperplasia, or those unsuitable for surgery, are optimally treated medically with mineralocorticoid receptor antagonists.